2022
DOI: 10.21203/rs.3.rs-1268531/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the α-synuclein PET Radiotracer (d3)-[11C]MODAG-001 in Pigs

Abstract: Background:A positron emission tomography (PET) radiotracer to neuroimage α-synuclein aggregates would be a crucial addition for early diagnosis and treatment development in disorders such as Parkinson's disease, where elevated aggregate levels is a histopathological hallmark. The radiotracer (d3)-[11C]MODAG-001 has recently shown promise for visualization of α-synuclein pre-formed fibrils (α-PFF) in rodents. We here test the radiotracer in a pig model where proteins are intracerebrally injected immediately be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…MODAG-001 in αSyn-inoculated pigs and demonstrated sufficient brain uptake of the tracer [35]. Ono et al reported that [ 18 F]C-05-05, a compound developed based on the tau imaging tracer PBB3 structure, showed specific detection of pS129 antibody-positive phosphorylated αSyn in an αSyn-inoculated mouse model as well as in an αSyn-inoculated nonhuman primate model [34].…”
Section: Raval Et Al Recently Reported a Further Evaluation Of (D3)-[...mentioning
confidence: 99%
“…MODAG-001 in αSyn-inoculated pigs and demonstrated sufficient brain uptake of the tracer [35]. Ono et al reported that [ 18 F]C-05-05, a compound developed based on the tau imaging tracer PBB3 structure, showed specific detection of pS129 antibody-positive phosphorylated αSyn in an αSyn-inoculated mouse model as well as in an αSyn-inoculated nonhuman primate model [34].…”
Section: Raval Et Al Recently Reported a Further Evaluation Of (D3)-[...mentioning
confidence: 99%